THE FREQUENCY OF ENGLISH LANGUAGE TEACHERS USING SOME INTERNET APPLICATIONS IN TEACHING READING COMPREHENSION SKILLS - Mowaffaq Mohammad Momani; Abdulelah Abdulqader Al Farhan; Hassan mohammed Al Qarni (European Scientific Journal, ESJ, 2015)
Teaching reading comprehension in Saudi Arabia had the attention of researchers and linguists. It is obvious that reading as a receptive skill is essential to allow learners produce proper language, this encouraged researchers to start investigating this area. In addition, the advent of computer and internet has positively affected education and teaching. Therefore, this study will examine the frequency of English language teachers using some Internet applications in teaching reading comprehension skills in the city of Tabuk. The population of the study involves 32 teachers from the intermediate grade at the city of Tabuk during the academic year 1435\1436 AH – 2014/ 2015 AD. In order to answer this research question, researchers design a questionnaire to discover the frequency of English language teachers using some internet applications (Dave's ESL Cafe, ESL Galaxy) in teaching reading comprehension skill. The analysis of data collected by this questionnaire shows the high frequency of using internet applications in teaching reading comprehension among the Saudi English language teachers at the Saudi Intermediate schools in Tabuk. Moreover, Saudi teachers are enthusiastic about using internet applications in teaching reading, as they secure activities and well-designed teaching materials. Finally, the findings of this study proved the relationship between using some Internet applications and the efficiency of teaching reading comprehension